2019
DOI: 10.1186/s13765-019-0424-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of headspace–SPME and SPME-Arrow–GC–MS methods for the determination of volatile compounds in Korean salt–fermented fish sauce

Abstract: A new solid phase microextraction (SPME)-Arrow method was evaluated for the analysis of volatile compounds in kanari-aekjeot, a Korean traditional salt-fermented sand lance sauce, and compared it to the standard headspace-SPME method. Factors observed to affect the extraction, including the fiber used, extraction temperature, extraction time, and NaCl concentration were carefully optimized. The Carboxen/Polydimethylsiloxane fiber exhibited the highest extraction efficiency for both analytical methods and was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…These headspace techniques are optimized in terms of several extraction parameters including fiber type, extraction temperature, extraction time, desorption time, salt content, pH, and the possible interactions between independent variables, which can significantly affect the extraction efficacy. [9][10][11][12][13][14][15][16] All experiments were performed in triplicate and the experimental conditions were optimized on the basis of normalized peak areas.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These headspace techniques are optimized in terms of several extraction parameters including fiber type, extraction temperature, extraction time, desorption time, salt content, pH, and the possible interactions between independent variables, which can significantly affect the extraction efficacy. [9][10][11][12][13][14][15][16] All experiments were performed in triplicate and the experimental conditions were optimized on the basis of normalized peak areas.…”
Section: Resultsmentioning
confidence: 99%
“…[32] In addition to food matrices, HS-SPME-Arrow extraction has been applied to determine volatile compounds in Korean salt-fermented fish sauce, providing better sensitivity and robustness. [11] Barreira et al [33] reported that SPME-Arrow improved the extraction efficacy of VOCs in the atmosphere with an up to 2-fold increase. The SBSE, one of microextraction technique, can also provide high sensitivity of analysis.…”
Section: Evaluating Sensitivity and Reproducibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the peak area of all volatile compounds extracted from soy sauce increased by approximately 4-40 times on using SPME Arrow as compared to conventional SPME (Table 1). Since SPME Arrow contains greater amount of adsorbent to extract more efficiently than SPME, its sensitivity was superior to that of SPME [31]. This technology can be used to extract the same amounts of analytes twice as fast as SPME, and the fiber geometry and materials can be optimized to increase F I G U R E 5 Reproducibility of the tested PA SPME Arrow and PA SPME fibers for peak area: average vs. standard deviation of RSD of 21 confirmed volatile organic compounds in soy sauce robustness and fiber lifetime.…”
Section: Analysis Of Volatile Organic Compounds In Soy Sauce Using Somentioning
confidence: 99%